The Indian runner [videorecording] - Bannon, Stephen K.; Bisgeier, Mark; Mount, Thom; Penn, Sean (The Mount Film Group [producer], 1991)
A moving story of two dynamic and very different brothers coming to terms with the meaning of life and the challenge of change in the restless and relentless atmosphere of post-Vietnam America.